2015
DOI: 10.3892/ijo.2015.3299
|View full text |Cite
|
Sign up to set email alerts
|

CD73 as a therapeutic target for pancreatic neuroendocrine tumor stem cells

Abstract: Identification and purification of cancer stem cells (CSCs) lead to the discovery of novel therapeutic targets; however, there has been no study on isolation of the CSC population among pancreatic neuroendocrine tumors (pNETs). This study aimed to identify pNET CSCs and to characterize a therapeutic candidate for pNET CSCs. We identified CSCs by aldehyde dehydrogenase (ALDH) activity in pNET clinical specimens and cell lines. We verified whether or not these cells have the stemness property in vivo and in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Moreover, cases involving tumors <10 mm in size with lymphatic and venous invasions are at high risk of lymph node metastasis with regard to colorectal NENs (39). It has also been reported that the immunohistochemical CD73 expression status was significantly correlated with invasion into adjacent organs in pNENs (14). In the present study, lymphatic and venous invasions were more frequent in the NEC group than in the NET group.…”
Section: Who 2010 Classification ------------------------------------supporting
confidence: 61%
See 2 more Smart Citations
“…Moreover, cases involving tumors <10 mm in size with lymphatic and venous invasions are at high risk of lymph node metastasis with regard to colorectal NENs (39). It has also been reported that the immunohistochemical CD73 expression status was significantly correlated with invasion into adjacent organs in pNENs (14). In the present study, lymphatic and venous invasions were more frequent in the NEC group than in the NET group.…”
Section: Who 2010 Classification ------------------------------------supporting
confidence: 61%
“…Recent studies identified CD73 as not only a unique biomarker for pNENs cancer stem cells but also a novel molecular target for pNENs therapy (14). CD73 expression is also associated with poor prognosis in several types of tumors (31), including colorectal cancer (32), gastric cancer (33), gallbladder cancer (34), serous ovarian cancer (35), triple negative breast cancer (36), and malignant melanoma (37).…”
Section: Who 2010 Classification ------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these studies, many human tumors overexpress CD73 and associates with poor prognosis (36,(73)(74)(75)(76)(77)(78). CD73 is also linked to drug resistance, epithelial-to-mesenchymal transition (EMT), and cancer cell proliferation and stemness (76,(79)(80)(81)(82)(83)(84). Tumors also grow slower in A2BR-deficient mice and mice treated with A2BR antagonists (85)(86)(87).…”
Section: Cd73 and Adenosine Receptor Activity Promotes Immunosuppressionmentioning
confidence: 79%
“…Studies of CD73 in human PDAC tissue have only recently emerged ( Table 2). CD73 is upregulated in PDAC compared to normal pancreatic tissue and correlates with increased tumor size, advanced stage, lymph node involvement, metastasis, and poor prognosis (77,80,172). While PDAC tumors are 100% positive for CD73 expression (172), interesting staining patterns for CD73 are seen.…”
Section: Pancreatic Cancermentioning
confidence: 99%